O processo de planejamento municipal em Brumadinho/MG: avanços e permanências em situação de minero-dependência - Juliana Godoy Corrêa de Araújo (2022)
The research seeks to analyze the municipal planning process of Brumadinho in order to understand if and how the issue of mining, the main economic activity and socio-environmental problem of the municipality, has been addressed. Located in the Quadrilátero Ferrífero and belonging to the RMBH, the municipality of Brumadinho had its first Master Plan instituted in 2006, which is still in effect today. After two revision proposals, in the years 2012 and 2016, the rupture of the tailings dam at the Córrego do Feijão mine, in January 2019, justified a new revision of the Master Plan with the purpose of incorporating the social and environmental problems after the disaster. Understanding the socio-environmental issue in Brumadinho in its interscalar dimension and inserted in a situation of mining-dependence, we seek to assess what were the changes and permanences in the planning process before and after the disaster and if, in fact, there were advances in the instruments regarding to approach socio-environmental problems and to balance the interests of the local community involved, and also to discuss one of the limits identified in the performance of municipal planning in the face of the articulation of the great economic interests of mining companies in the municipal territory.